In Vivo and In Vitro Analyses of Novel Peptidomimetic Disruptors for the Serotonin 5-HT2C Receptor Interaction With Phosphatase and Tensin Homolog - Soto, Claudia A.; Du, Huang-Chi; Fox, Robert G.; Yang, Taegyun; Hooson, James; Anastasio, Noelle C.; Gilbertson, Scott R.; Cunningham, Kathryn A. (Frontiers in Pharmacology, 2019)
Hypofunction of the serotonin (5-HT) 5-HT2C receptor (5-HT2CR) has been implicated in a variety of disorders including substance use disorders. As such, approaches to enhance 5-HT2CR signaling display therapeutic potential. In the present study, we show that disruption of the 5-HT2CR interaction with the protein phosphatase and tensin homolog (PTEN) via peptidomimetic-based protein-protein interaction disrupters enhances 5-HT2CR-mediating signaling in vitro and potentiates selective 5-HT2CR agonists in behavioral rodent models. Overall, the present study provides further evidence that 5-HT2CR activity can be modulated through an allosteric protein-protein interaction. This work provides the groundwork for the continued exploration of protein-protein interactions that can allosterically modulate this critical receptor and other important GPCRs for new therapeutic development through mechanisms that may display clinical utility.